Evaluation Of Social License To Operate (Slo) In Three Blocks Of Pt. Xyz - Aisha R Tazkia; Dita Oki Berliyanti (International Journal Labs, 2024)
Mining companies around the world often face high socio-political risks, especially due to their impact on the environment. One indicator of this risk is the Social License to Operate (SLO). This study examines how the community accepts PT. XYZ in terms of achieving the Social License to Operate (SLO) as part of the company's commitment to community involvement. This study is a qualitative study, where the study was conducted by distributing questionnaires to community groups first to obtain qualitative data, then continued with interviews and focus group discussions (FGD) to gain broader and deeper insights into the perceptions of each community group regarding expectations related to the company's programs. The results of the study will then be linked to the relevant Sustainable Development Goals to see the relationship and contribution to the company's sustainability goals.